Comparative evaluation of shear bond strength of different bracket base designs in dry and wet environments - Mehta O; Saini S; Dahiya A (Wolters Kluwer Medknow Publications, 2008)
One hundred and thirty five extracted premolars were selected and bonded with three types of brackets with different bracket base designs viz. Gemini (foil mesh), Miniature twin (Laser etched) and Mini Dynalocks (Integral base). These brackets were bonded with Transbond XT adhesive using two types of primers viz. Conventional Transbond XT in dry conditions and M.I.P in dry and wet environments. The specimens were tested for SBS using Instron machine at C.I.P.E.T. (Amritsar), Punjab. Results were statistically analyzed. Results and Discussion: The Miniature twin brackets revealed higher SBS values as compared to Gemini and Mini Dynalock in dry and wet conditions. All the groups showed higher SBS values in dry conditions as compared to wet conditions respectively. The Gemini and Mini Dynalock brackets showed very little difference of SBS values. Conclusion: Miniature twin brackets with laser etched bracket base in dry and wet environments have revealed the highest SBS values. All the groups have revealed clinically acceptable SBS value of above 8 MPa in moist conditions.